MAPPING THE EFFECT OF STORING PARAMETERS ON THE QUALITY OF CLOVES - Farisan Silmi, Fadian
Clove (Syzygium aromaticum) is a type of spice from Indonesia which is commonly found in several regions in Indonesia. The chemical compounds in the clove are secondary metabolite products which are known to cause the characteristic of the clove's taste and aroma. The characteristics of the clove are influenced by the environmental conditions of the place of planting and harvesting and postharvest treatment such as storage time, temperature, and humidity of clove’s storage. One method for studying the metabolic characteristics of a biological system is metabolomics. In metabolomic analysis, several analytical methods are used for measurements such as gas chromatography as a separation technique of several volatile compounds and mass spectrophotometry as a detector which functions to interpret the results of gas chromatography from the sample. This study aims to describe the effect of storage time on the quality of cloves from various regions and map the clove metabolism based on the composition of its metabolites. The clove is extracted using Pressurized Liquid Extraction and solvent concentration using Solid Pressurized Extraction. Extraction results are injected into the GC-MS device and the results of mass spectrometry will be processed statistically by the Principal Component Analysis. The scope of this study includes clove species from Bali and Tolitoli, variations in storage time in the range of 61 weeks and different storage locations, namely in the warehouse area with a temperature of 29 ± 2oC at 30% relative humidity and laboratory area with 24 ± 2oC in relative air humidity 9%. The results of the study showed that statistically with a 2-dimensional PCA score of 54.99%, in Bali clove until storage time for 61 weeks showed no signs of stability in the metabolites. Whereas in cloves Tolitoli was statistically assessed with a 2-dimensional PCA score of 51.18%, at the 40th week of storage showed metabolite stability.